ROLE AND MANAGEMENT OF POTASSIUM NUTRIENT FOR FOOD PRODUCTION IN INDONESIA - Subandi, Subandi (+622518321746, 2013)
The big number of as well as the increase in Indonesian population offers challenges in supplying foods in terms of quantity, variety, and quality. This situation requires increasingly attention because at present the country is still importing rice, maize, and soybean in a significant amount. In Indonesia, efforts to increase food production highly depend on supplying nutrients of crops, among of them is potassium (K). Potassium is essentially required in a high amount by crops to grow normally and to produce yield optimally. Potassium is one of the determining factor in obtaining quantity and quality of agricultural products due to the important roles in: (1) photosynthetic process and translocation of its products; (2) protein syntheses; and (3) increasing crop tolerance to biotic (pests/diseases) and abiotic (drought and Fe toxicity) stresses, as well as determining physical and chemical properties of agricultural products. Therefore, K in the soil and fertilizers, and agricultural resources should be managed properly through several ways, i.e.: (1) preparing map of soil K status as a guidance in implementing specific recommendation of K fertilizer application; (2) using agricultural by-products containing K such as rice straw, maize and soybean stove, and animal manure; (3) decreasing erosion and K leaching, and (4) optimizing aeration and water holding capacity of soil.